سيميائية الأهواء في خطاب خاتم الأنبياءﷺ دراسة في فن التأثير والإقناع: The Semiotics of Passions in the Discourse of the Seal of the Prophets (PBUH): A Study in the Art of Influence and Persuasion - نادية لقجع جلول سايح (الدراسات الإسلامية, 2025)
This study applies a semiotic–rhetorical framework grounded in A. J. Greimas and Jacques Fontanille’s Semiotics of Passions to examine the transformative power of affective language in the discourse of Prophet Muḥammad (PBUH). It investigates how the Prophet strategically employed affect-laden rhetoric to effect deep cognitive and behavioral transformation among diverse social groups, ultimately unifying them into an ethically grounded and emotionally coherent Ummah. The research posits that Prophetic discourse functions as a highly sophisticated persuasive model rooted in an acute understanding of human nature and its passions (ahwāʾ). Using a descriptive–analytical method, the study analyzes selected ḥadīth texts, focusing on the pathēmic sense-effects they generate—effects central to persuasion and moral formation. The findings reveal that the Prophetic discourse orchestrates affect across three interrelated axes aligned with the higher objectives (maqāṣid) of Islamic law. Through the axis of attraction, the discourse mobilizes hope (rajāʾ) and optimism by invoking future reward and using vivid imagery that stabilizes the emotions of early believers. Through the axis of rejection, it employs warnings and expressions of awe (rahbah) to provoke introspection, repentance, and ethical vigilance, often through striking semantic contrasts between worldly heedlessness and the gravity of the unseen (ghayb). Through the axis of balance, it cultivates compassion (raḥmah) and social solidarity via evocative narratives, potent rhetorical figures, and reminders of divine reciprocity. The study also highlights the semiotics of yearning (shawq), demonstrating how the Prophet’s affective distinction between “Companions” (aṣḥāb) and “Brethren” (ikhwān) generates an enduring emotional horizon that extends his rhetorical influence across time and space.